FORMULATION AND EVALUATION OF OPHTHALMIC GEL BASED ON DRUG-POLYMER-POLYMER TERNARY INTERACTION - S Bhoyar, Bhushan; T Patil, Arun (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: The objective was to enhance the amount of active substance reaching the target tissue or exerting a local effect in the cul-de-sac, the approach we use is the application of in-situ gelling systems or phase transition systems, which are instilled in a liquid form and shift to a gel or solid phase in the cul-de-sac. The present study will focus on the development of formulation of ophthalmic gels. The polymer physicochemical properties were studied for the improvement in gel characteristics. Methods: The formulations were varied by the amount of the anionic and cationic polymer concentration. The 10 and 20-fold excess anionic polymer were used. The 10 and 20-fold excess anionic polymer were used. Further cationic polymers were utilized to see any ternary interaction between drug and polymers. Results: From the present study it could be shown that most of the formulations were isotropic and could be clearly separated from the anisotropic ones which were situated at the cationic side of the phase diagram only as well as at 10% polyvinyl alcohol. Furthermore, excess 20HA, 10PAA, and 20PAA as well as HCS (HCS/20PAA) contributes to improve drug release control. Conclusion: The above formulation of were found to be quite stable and useful in the novel format of sol-gel transformations. Further, the physical characteristics gels show better tolerability with anionic and cationic polymer. Keywords: Cationic, Anionic, Poloxamer, Sol-gel.